Non-discretionary monetary policy: The answer for transition economies? - Elham Mafi-Kreft; Steven F. Kreft (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
It is a well-established fact that monetary institutions help shape the macroeconomic environment of countries by stabilizing prices. In the early 1990s, transition economies had the opportunity to rearrange their monetary institutions to better achieve low levels of inflation. Those economies had several prominent monetary arrangements to choose from, such as sovereign central banks or currency boards. This paper surveys the monetary institutions currently in place in several transition economies and compares them based on their ability to control inflation. More specifically, we intend to test whether the transition economies have better inflation performance when they import the monetary policy of a credible central bank.
Keywords: 330; Transition economies; currency board; European monetary union